Science teaching in the elementary school - Bangloy, Purificacion P. 1931- (1959)
Determination of the present requirements and materials in science teaching and the preparation of teachers for science instruction was the aim of this study. After the results were determined, a program was proposed to be adopted for effective elementary science instruction.